Using Text via Dialectical Journals to Nurture Liminal Spaces in Teacher Education. (October 2022) - Dodman, Stephanie L.; Holincheck, Nancy; Brusseau, Rebecca
This article shares the findings of a study examining the use of dialectical journals as liminal spaces for the development of critical reflection in practicing teachers. In an online graduate course on critical teacher inquiry designed to foster teachers as antiracist multicultural educators, teachers engaged in dialogue with themselves as they responded to self-selected text segments in assigned readings throughout the course. Using Mezirow's theory of transformation and specifically the typology of critical reflection of assumptions and critical self-reflection of assumptions, we analyzed the online dialectical journals of 23 teachers to better understand how their engagement with key texts both represented and influenced their reflective development and engagement in transformational learning. We conclude the journals to be powerful liminal spaces for teachers to engage in reframing of their assumptions.